Carotid Body: A New Target for Rescuing Neural Control of Cardiorespiratory Balance in Disease - Rodrigo Del Rio (Frontiers Research Topics, 2016)
The carotid body (CB) is in charge of adjusting ventilatory and cardiovascular function during changes in arterial blood gases. Regardless this essential function, the CB has been implicated in the sensing of other physiological signals such as changes in blood flow and glucose levels. More important, malfunction of the CB chemoreceptors has been associated with the progression and deterioration of several disease states such as hypertension, heart failure, renal failure, insulin resistance, diabetes and sleep apnea. Although the mechanisms involved in the alterations of the CB function in pathophysiology are currently under intense research, the development of therapeutic approaches to restore normal CB chemoreflex function remains unsolved. Recent studies showing the effect of CB denervation in pathophysiology have unveiled a key role of these arterial chemoreceptors in the development of autonomic imbalance and respiratory disturbances, and suggest that targeting the CB could represent a novel strategy to improve disease outcome. Unfortunately, classical pharmacotherapy intended to normalize CB function may be hard to establish since several cellular pathways are involved in the CB dysfunction. Augmented levels of angiotensin II, endothelin-1, cytokines and free radicals along with decreases in nitric oxide had all been related to the CB dysfunction. Moreover, changes in expression of angiotensin receptors, nitric oxide synthases and cytokines that take place within the CB tissue in pathological states also contribute to the enhanced CB chemoreflex drive. It has been shown in heart failure, hypertension and obstructive sleep apnea that the CB becomes tonically hyper-reactive. During the progression of the disease this CB chemosensory facilitation process induces central nervous system plasticity. The altered autonomic-respiratory control leads to increased cardiorespiratory distress and the deterioration of the condition. The focus of this e-book will be to cover the role of the CB in pathophysiology and to provide new evidence of the pathways involved in the maladaptive potentiation of the CB chemoreflex function. In memory of Professor Mashiko Shirahata and Professor Constancio Gonzalez.